Literatura infantil: alfabetização e letramento - AMORIM, Vera Lúcia da Silva (2024)
His work of completion is themed Children's Literature: Literacy and Literacy and was conducted in Elementary School "St. Francis Xavier ," attempts to answer the problem of how children's literature can help in the Reading Process of students in the classes of 1st and 2nd year of elementary school this educational institution, verifying how teachers work the learning process of writing and reading, as theoretical Magda Soares, Isabel Solé, Juracy Assmann Saraiva, among others. We noticed during the research that teachers are aware of the importance of literary practice in the classroom. We believe that the expected results were achieved because it is understood that literature must be present early in the experience of students, thereby facilitating the practice of reading and writing in literacy and literacy process.